AMIDES ISOLATED FROM THE LEAVES OF Piper tuberculatum Jacq. (Piperaceae) WITH ACETYLCHOLINESTERASE INHIBITION AND LARVICIDAL ACTIVITY AGAINST Aedes aegypti - Brenda R. C. Leocadio; Taynara S. Vale; Felipe M. A. da Silva; João V. C. O. Santos; Sergio M. Nunomura; André C. de Oliveira; Ingrity S. C. Sá; Rosemary A. Roque; Ana Paula A. Castro; Magno P. Muniz; Rita C. S. Nunomura (Química Nova)
Piper tuberculatum Jacq. is known to be a promising source of amides, which have shown remarkable biological activities. In this study, a phytochemical investigation of the leaves of P. tuberculatum was conducted, leading to the isolation of the amides cis-piplartine (1), piplartine (2), and 4,5-dihydropiperlonguminine (3). The structures of the compounds were determined through the analysis of 1D and 2D nuclear magnetic resonance (NMR), mass spectrometry (MS), and high-resolution mass spectrometry (HRMS), as well as data comparison with the literature. The isolated amides were tested for acetylcholinesterase (AChE) inhibition assay and larvicidal activity against Aedes aegypti. The significant larvicidal activity of the isolated amides, along with the AChE inhibition results, indicate that the larvicidal activity is related to the inhibition of this enzyme. These results suggest that these amides are promising larvicidal compounds.